Examining gender role attitude as a moderator of personality, social support, and childcare responsibilities in women’s work-life balance - Shaleh, Abdul Rahman; Nuraini, Putri (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
The participation of women in the workforce creates challenges and problems. Those with various roles in their lives must be good at playing and balancing these successfully. This study focuses on the work-life balance factor by exploring the predictor factors including personality, family social support, and childcare responsibilities, as moderated by gender role attitude. A work/ nonwork interference and enhancement scale, mini-IPIP, gender role beliefs scale, and social support scale were developed for the data collection. A sample of 220 married female workers was identified using purposive sampling. The data analysis, which used multiple regression and a modgraph, shows a significant effect of personality, social support, and childcare responsibilities on the work-life balance moderated by gender role attitude. Four independent variables with significant influence are neuroticism, openness to experiencing family support, gender role attitude and there is a moderating effect on neuroticism and family support. The implication is the need to provide a comfortable work environment and arrangement of work patterns so that women's work-life balance can be achieved positively.